Digitalization Android-based Interactive Learning Media in Geography for High School Students - Lasfika, Yudith Tia; Widyastono, Herry; Yamtinah, Sri (Journal of Education Technology, 2022)
The lack of innovative learning media for geography material is something that needs to be updated immediately. In line with that, the high usage smartphones with the Android operating system has the potential to be used as a basis for making an innovation of learning media. Learning geography plays a role in providing knowledge, skills and attitudes about caring for the environment, which is currently seen that very few students have an attitude of caring for the environment, through the form of integration between learning materials and Android technology, it can be a breakthrough for learning activities. Therefore, this study aims to develop an Android-based interactive digital learning media innovation for geography learning in high school. This research approach is research and development (RnD) which adopts the ADDIE model, focusing on the development and assessment of android-based interactive media products. This research will involve one media expert, one material expert and three teachers. The data collection technique used a non-test technique with the instrument, namely a validation questionnaire or feasibility test for media experts, material experts and teachers. The results of the questionnaire will be analyzed descriptively and with using percentages. The results showed that android-based interactive media obtained an average percentage score of 96% of media experts and three teachers who were included in the 'decent without revision' category, while the results of material experts and three teachers obtained an average score of 85.8% which was included in the category 'feasible without revision', with android-based interactive media developed in this study obtained the decision that it was feasible to be tested and used for students in the learning process.